2021
DOI: 10.1021/acs.accounts.1c00600
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-Phase Processing of Metal–Organic Frameworks

Abstract: Porous metal−organic frameworks (MOFs), formed from organic linkers and metal nodes, have attracted intense research attention. Because of their high specific surface areas, uniform and adjustable pore sizes, and versatile physicochemical properties, MOFs have shown disruptive potential in adsorption, catalysis, separation, etc. For many of these applications, MOFs are synthesized solvothermally as bulk powders and subsequently shaped as pellets or extrudates. Other applications, such as membrane separations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…To avoid post-deposition treatments, Ameloot et al fabricated a uniform and compact ZIF-8 film through a vapourphase transformation from ALD ZnO films to ZIF-8, as shown in Figure 1b. 81 A recent review by Su et al 82 is suggested for further insight regarding this strategy. The solvent-free strategy makes ALD/MLD appealing for the microelectronics industry, 86 as it can lead to a meticulous tuning of thickness and possess a good potential for scaleup.…”
Section: Atomic/molecular Layer Depositionmentioning
confidence: 99%
“…To avoid post-deposition treatments, Ameloot et al fabricated a uniform and compact ZIF-8 film through a vapourphase transformation from ALD ZnO films to ZIF-8, as shown in Figure 1b. 81 A recent review by Su et al 82 is suggested for further insight regarding this strategy. The solvent-free strategy makes ALD/MLD appealing for the microelectronics industry, 86 as it can lead to a meticulous tuning of thickness and possess a good potential for scaleup.…”
Section: Atomic/molecular Layer Depositionmentioning
confidence: 99%
“…This later approach is less desirable, as it somehow cancels the great advantage of all-gas phase processing. Indeed, vapour phase synthesis of MOFs thin films is a highly attractive strategy when contemplating MOF integration into devices [22][23][24] . In conjunction with reducing environmental impact, solvents should be avoided for device fabrication regarding the contamination and corrosion risks 25 as well as the generated surface tension during evaporation 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, one key issue in the application of MOF in nano‐vehicles involves nanoscale synthesis, [ 7 ] especially for nanoscale MOF with a monodispersed morphology. This is a challenge because conventional soluble metal salt precursors are difficult to control spatially, always leading to bulky MOF, [ 8 ] which limits the application of MOF serving as drug delivery vehicles to combat intracellular bacteria.…”
Section: Introductionmentioning
confidence: 99%